Internal branding as a tool for integrated organisational alignment (Communicare: Journal for Communication Studies in Africa, 2022)
Within an evolving business environment, it is central to the continuing success of organisationsthat internal communication be taken into consideration in the quest to increase organisationalcompetitive advantage. This paper explores the importance of an alignment existing betweeninternal organisational values and the external organisational image. As such, to guaranteethe promotion of employee satisfaction through an internal organisational alignment strategy,improvement should be made to internal communication strategies. As it implemented internalbranding initiatives so as to align internal stakeholders with the core organisational values and itsexternal corporate brand image, Absa Bank is the chosen sample. Through qualitative research,the participants concur that the aim of the internal branding initiative is to improve the quality ofservice rendered, to retain external customers, and to impact positively on the bank’s profitability.Based on the research, the data analysis reveals that a key contribution is the conceptualisationof the term ‘integrated organisational communication’.